2014
DOI: 10.1093/europace/euu220
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial ablation vs. left atrial concomitant surgical ablation for treatment of atrial fibrillation: a meta-analysis

Abstract: Biatrial and LA ablations produced comparable 30-day and late mortality but LA was associated with significantly reduced permanent pacemaker implantation rates. Biatrial ablation appeared to be more efficacious than LA ablation in achieving SR at 1 year, but this difference was not maintained beyond 1 year. Trends appear to be driven by the preferential selection of long-standing and persistent AF patients for the BA approach. Future randomized studies of adequate follow-up are required to validate risks and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 28 publications
1
42
1
6
Order By: Relevance
“…Although promising, these results are suboptimal, particularly in patients with persistent and long-standing persistent AF (10)(11)(12), which is partly due to the lack of transmurality in some lesions as well as gaps in ablation. In some cases of persistent or long-standing AF or AF refractory to medical and catheter ablation, surgical ablation offers an alternative option (13)(14)(15)(16)(17)(18). In the FAST randomized controlled study (19), it was demonstrated that the video-assisted surgical approach may achieve superior success rates to catheter ablation in the short term, although the patient is at risk of higher procedural complications including pneumothorax, major bleeding and pacemaker requirements.…”
Section: Original Articlementioning
confidence: 99%
“…Although promising, these results are suboptimal, particularly in patients with persistent and long-standing persistent AF (10)(11)(12), which is partly due to the lack of transmurality in some lesions as well as gaps in ablation. In some cases of persistent or long-standing AF or AF refractory to medical and catheter ablation, surgical ablation offers an alternative option (13)(14)(15)(16)(17)(18). In the FAST randomized controlled study (19), it was demonstrated that the video-assisted surgical approach may achieve superior success rates to catheter ablation in the short term, although the patient is at risk of higher procedural complications including pneumothorax, major bleeding and pacemaker requirements.…”
Section: Original Articlementioning
confidence: 99%
“…Patients with new-onset paroxysmal AF can achieve AF ablation with pulmonary vein isolation lesion, whereas those with recent onset paroxysmal AF or those undergoing non-right heart surgery can achieve ablation with a left atrial lesion. Patients with longstanding symptomatic AF or AF in young patients undergoing right heart surgery are likely to benefit from biatrial lesions-which are the most effective (114,115).…”
Section: Types Of Lesionsmentioning
confidence: 99%
“…16 Limiting ablations to the left atrium has the potential for less postoperative bradycardias and atrial flutters. A meta-analysis of 10 randomized and observational studies 17 showed a significant reduction in the need for permanent pacing with left atrial ablation compared with biatrial ablations. Biatrial ablation was more effective in maintenance of sinus rhythm at 1 year, although this advantage was not maintained beyond the first year.…”
Section: Outcomes In Comparative Studiesmentioning
confidence: 99%